KELIR DIGITALISASI : STRATEGI PRODUKSI VIDEO DOKUMENTER PEMENTASAN WAYANG KULIT DALANG MUDA KI PANDU NUR PRASTIYO DALAM KONTEKS DIGITAL PELESTARIAN BUDAYA - Heriyanto Atmojo (Akademi Seni dan Desain Indonesia Surakarta, 2025)
Documentation of wayang kulit performance art needs to adapt to changes in the media consumption patterns of the younger generation in order to remain relevant and in demand. This study proposes a documentary video production strategy that combines a modern audiovisual approach, engaging narratives, and strategic digital distribution. Some of the main approaches include the use of dynamic cinematography, a strong storyline with a storytelling approach, embedding subtitles and educational infographics, and utilizing digital platforms such as YouTube, Instagram, and TikTok to reach a wider audience. In addition, interactivity through social media and collaboration with content creators also strengthen the involvement of the younger generation. This strategy aims not only to document traditional arts, but also to revive them in the digital space as part of adaptive and sustainable cultural preservation. Keywords: Shadow puppets, digital documentation, young generation, documentary video, cultural preservation